Trocando MEIA por SEIS? A variável SEIS em Conselheiro Lafaiete-MG - Vanessa Aparecida de Almeida Dornelas (2018)
The aim of this research is the variants seis ~ meia ~ meia dúzia at Conselheiro Lafaiete city, in Minas Gerais, Mineiro Speech, according to Zágari (1998). There are contexts in which seis do not vary with meia. Therefore, there are conditions of variance and invariance. We have adopted the Language Variation and Change Theory (LABOV, [1972] 2008). The Multisystemic Theory according to Castilho (2010) is also adopted. The reading of numeric sequences was recorded. The numbers are related to: Telephone, CEPs (Brazilian postal code), Address, Book chapter, Bank password, Car plate, Bus, Magazine, Price, Birthday, Time indicator, Test grading, Age, Bar code and ISBN. It has been observed change towards the progress of the use of the variant seis in some themes. It has been found deslexicalization of the item meia.